The false prince - Nielsen, Jennifer A. (Nielsen, Jennifer A. Ascendance series, 2012)
In a discontented kingdom, civil war is brewing. To unify the divided people, Conner, a nobleman of the court, devises a cunning plan to find an impersonator of the king's long-lost son and install him as a puppet prince. Four orphans are recruited to compete for the role, including a defiant boy named Sage. Sage knows that Conner's motives are more than questionable, yet his life balances on a sword's point -- he must be chosen to play the prince or he will certainly be killed. But Sage's rivals have their own agendas as well. As Sage moves from a rundown orphanage to Conner's sumptuous palace, layer upon layer of treachery and deceit unfold, until finally, a truth is revealed that, in the end, may very well prove more dangerous than all of the lies taken together.